2020
DOI: 10.5334/labphon.195
|View full text |Cite
|
Sign up to set email alerts
|

The imitation of coarticulatory timing patterns in consonant clusters for phonotactically familiar and unfamiliar sequences

Abstract: This paper investigates to what extent speakers adapt to unfamiliar consonant cluster timing patterns. We exploit naturally occurring consonant overlap differences between German and Georgian speakers' productions to probe the constraints that language-specific patterns put on the flexibility of cluster articulation. We recorded articulography data from Georgian and German speakers imitating CCV clusters as produced by a German and Georgian audio model, respectively. The German participants adapted their relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…By contrast, in the case of gestural models of syllable structure, the fact that the increased gestural anticipation of codas is variable in the phonological contexts (geminates vs. clusters) can only be accounted for if the timing relationships between gestures within the syllable are conceived of as very general templates over which language-, context-, and possibly also speaker-specific constraints apply. As a matter of fact, this view is receiving increasing support from cross-linguistic investigation of a variety of phenomena related to the internal organization of syllables (e.g., Chen et al, 2017; Pouplier, 2015; Pouplier et al, 2020), showing the role of phonetic segmental factors in shaping the articulatory cohesion within the syllable. Gestural cohesion effects spanning syllable boundaries also call for a more gradient view of articulatory syllabification.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in the case of gestural models of syllable structure, the fact that the increased gestural anticipation of codas is variable in the phonological contexts (geminates vs. clusters) can only be accounted for if the timing relationships between gestures within the syllable are conceived of as very general templates over which language-, context-, and possibly also speaker-specific constraints apply. As a matter of fact, this view is receiving increasing support from cross-linguistic investigation of a variety of phenomena related to the internal organization of syllables (e.g., Chen et al, 2017; Pouplier, 2015; Pouplier et al, 2020), showing the role of phonetic segmental factors in shaping the articulatory cohesion within the syllable. Gestural cohesion effects spanning syllable boundaries also call for a more gradient view of articulatory syllabification.…”
Section: Discussionmentioning
confidence: 99%
“…This question is particularly pertinent for intrusive vowels, since such vowels, by definition, do not contrast with anything, including the absence of themselves, and so appear at first blush to be functionally deficient in an important sense. Gestural timing varies from language to language, even in otherwise identical consonant clusters (Pouplier et al, 2020), so it could be supposed that all non-phonemic vowels, even very long ones, are simply due to differing degrees of gestural overlap. But this is scarcely an explanation, and it has been suggested that inserted vowels may provide formant cues for adjacent consonants (Tabain & Breen, 2011).…”
Section: Intrusive Vowelsmentioning
confidence: 99%